Contextualizing Christ Through Chinese Dining Tradition - Siwalette, Michelle Kezia (KnE Social Sciences, 2024)
The cultural and traditional diversity in Indonesia indirectly aids in making the process of spreading the gospel more accessible. Contextualization theology emerges as a viable option for disseminating the gospel message, with the goal of making the gospel of Jesus Christ relevant in contexts that are easily understood in all human aspects. By bringing up the subject of "eating together," the author hopes to make it easier and more relevant for readers to understand Jesus Christ's love for mankind. Just as "eating together" is significant for the Chinese as a sign of family, love, and respect, Jesus declared to sinners. Keywords: Tuan Yan Fan, communal eating, contextual theology, evangelism, love